The timing of maternal depressive symptoms and child cognitive development: A longitudinal study - Evans, J; Melotti, R; Heron, J; Ramchandani, P; Wiles, N; Murray, L; Stein, A (2012)
Background: Maternal depression is known to be associated with impairments in child cognitive development, although the effect of timing of exposure to maternal depression is unclear. Methods: Data collected for the Avon Longitudinal Study of Parents and Children, a longitudinal study beginning in pregnancy, included self-report measures of maternal depression the Edinburgh Postnatal Depression Scale, completed on 6 occasions up to 3 years of age, and IQ of the index child (WISC) measured at aged 8 years. We used these data to assign women to 8 groups according to whether depression occurred in the antenatal, postnatal, preschool period, any combination of these times, or not at all. We compared a model comprising all patterns of depression (saturated model) with models nested within this to test whether there is a relationship between depression and child cognitive development and, if so, whether there is a sensitive period. We then investigated the relationship with child IQ for each model, following adjustment for confounders. Results: Six thousand seven hundred and thirty-five of 13,615 children from singleton births (49.5%, of eligible core sample) attended a research clinic at 8 years and completed a WISC with a score ≥ 70. A total of 5,029 mothers of these children had completed mood assessments over the 3 time periods. In unadjusted analyses, all three sensitive period models were as good as the saturated model, as was an accumulation model. Of the sensitive period models, only that for antenatal exposure was a consistently better fit than the accumulation model. After multiple imputation for missing data (to n = 6,735), there was no effect of postnatal depression on child IQ independent of depression at other times [-0.19 IQ points, 95% confidence interval (CI) -1.5 to 1.1 points]. There was an effect of antenatal depression (-3.19 IQ points, 95% CI: -4.33 to -2.06) which attenuated following adjustment (-0.64 IQ points, 95% CI: -1.68 to 0.40). Conclusions: The postnatal period is not a sensitive one for the effect of maternal depression on child cognitive development. © 2011 The Authors. Journal of Child Psychology and Psychiatry.